FUNCTIONAL EXERCISE ON PATIENTS’ REHABILITATION WITH PSOAS MUSCLE SPORTS INJURIES - Shi,Xiaolan (2022)
ABSTRACT Introduction Lumbar muscle strain is a chronic injury to soft tissues such as the lumbar muscles, ligaments, and fascia. Functional exercise has specific applications in treating lumbar muscle injuries caused by sports. However, analyses on the treatment results in the psoas muscle are inconclusive. Objective Analyze the clinical efficacy of functional exercise in treating psoas muscle dysfunction. Methods 10 athletes diagnosed with lumbar muscle strain received continuous training with a functional exercise protocol for two weeks, five times a week. Clinical efficacy was assessed by visual analog scale for pain score and Prokin254 for proprioception ability indices before and after treatment. The article adopts a mathematical statistics analysis method to analyze the therapeutic effect of motor function exercise with SPSS 13.0. Results Patients reported a reduction of pain in the muscles under exertion after functional exercise. The results were significantly different (P<0.05). Patients’ lumbar strength was significantly improved. This index has a considerable statistical difference (P<0.05). Conclusion Functional exercise showed a positive effect on the treatment of psoas muscle injury. The research results of this article can provide an effective training protocol for the rehabilitation of people with a psoas muscle strain. Evidence Level II; Therapeutic Studies - Investigating the result.